IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 SAMBAS TAHUN PELAJARAN 2025/2026 - Nurhul Syadikin; Hifza; Effiyadi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to describe the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) at Sambas State Junior Secondary School 1 during the 2025/2026 academic year, covering the aspects of planning, implementation and evaluation. This study employs a descriptive qualitative approach. Data were obtained through interviews, observations and documentation, with the primary data sources being the PAI teacher and pupils in Class VII A. Data validity was checked through triangulation of sources and techniques. Data analysis was carried out through data reduction, data presentation and drawing of conclusions. The research findings indicate that lesson planning was carried out through the development of teaching modules tailored to the Learning Outcomes (CP), learning objectives, pupils’ characteristics, and school conditions. During the implementation stage, teachers began to apply pupil-centred learning through group discussions, taharah practice, wudu and tayamum practice, as well as tasks/projects to reinforce akhlakul karimah. However, the lecture method was still used quite frequently due to time constraints. Assessment was carried out through the evaluation of attitudes, knowledge and skills, including worksheet tasks, daily tests, written tests, practical exercises, observations, end-of-semester assessments (PAS) and end-of-year assessments (PAT). The main challenges included limited teaching time, some pupils being less active or drowsy during the afternoon sessions, and the need to strengthen teachers’ understanding of the Merdeka Curriculum through training and seminars.